Factors Influence on Debt Maturity Structure (In Manufacturing Companies Registered on the IDX for the 2019 - 2021 Period) - Surbakti, Feryanto; Hadiprajitno, P. Basuki (Politeknik Siber Cerdika Internasional, 2024)
This study examines the effectProfit Management, Company Size, Asset Maturity, Leverage on Debt Maturity Structure(Manufacturing Companies Registered on the IDX for the 2019 - 2021 period). The research population is pThe population for this research is all publicly listed companies on the IDX for the 2019-2021 period. The samples were taken based on purposive sampling, which means the criteria used are as follows: (a) Manufacturing companies listed on the IDX for 2019-2021, (b) Financial reports are accessible, (c) The required variable data is available.Furthermore, to perform data analysis, multiple linear regression through the use of SPSS software as a tool is used in this study. The research results show that hhypothesis 1 earnings management (DA) has a sig value of 0.027<0.05 and β1 -0.170<0 then H1 is accepted, meaning that earnings management has a negative effect on the structure of debt maturity. Hypothesis 2 firm size (SIZE) has a sig value of 0.000<0.05 and β2 0.018>0, so H2 is accepted, meaning that firm size has a positive influence on the structure of debt maturity. Hypothesis 3: asset maturity (ASMAT) has a sig value of 0.000<0.05 and β3 0.528>0, so H3 is accepted, meaning that asset maturity has a positive influence on the debt maturity structure. Hypothesis 4 leverage (DAR) has a sig value of 0.510> 0.05, so H4 is rejected, meaning that leverage has no effect on the structure of debt maturity.